Shakespeare and Emotions
XII, 270 p. 7 illus.
Keywords: This collection of essays approaches the works of Shakespeare from the topical perspective of the History of Emotions. Contributions come from established and emergent scholars from a range of disciplines, including performance history, musicology and literary history.